Role of Three-Dimensional Printing (3DP) in Spinal Deformity Correction - Abdelaziz Zaki, Mohamed Reda; Abd Elfattah, Hassan Abd Elsalam; Abd Allah Salama, Hosny Hassan; Elsayed Abo Sleem, Mohamed Abd Elfatah (Journal of Neonatal Surgery, 2024)
Three-dimensional printing (3DP) has emerged as a transformative technology in modern medicine, enabling the conversion of radiological imaging data into precise, patient-specific anatomical models. In spine surgery, 3DP has gained significant attention due to its ability to enhance preoperative planning, improve surgical accuracy, and facilitate the development of customized implants and instrumentation. With continuous advancements in printing techniques and biomaterials, 3DP is increasingly integrated into the management of complex spinal pathologies, including deformities, trauma, malignancies, and degenerative conditions...